2015
DOI: 10.1016/j.virol.2014.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Discovery, diversity and evolution of novel coronaviruses sampled from rodents in China

Abstract: Although rodents are important reservoirs for RNA viruses, to date only one species of rodent coronavirus (CoV) has been identified. Herein, we describe a new CoV, denoted Lucheng Rn rat coronavirus (LRNV), and novel variants of two Betacoronavirus species termed Longquan Aa mouse coronavirus (LAMV) and Longquan Rl rat coronavirus (LRLV), that were identified in a survey of 1465 rodents sampled in China during 2011-2013. Phylogenetic analysis revealed that LAMV and LRLV fell into lineage A of the genus Betacor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
117
3
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(134 citation statements)
references
References 47 publications
(63 reference statements)
6
117
3
4
Order By: Relevance
“…Unlike other alpha-and betacoronavirus species, BetaCoV1 and the related mouse hepatitis virus (MHV) and HCoV-HKU1 do not seem to have ancestral links to bats. Several recent descriptions of novel BetaCoV1 members or relatives in rodents suggest them as primordial hosts (Hu et al, 2017;Lau et al, 2015;Wang et al, 2015). HCoV-OC43 was found to have tropism for neural cells in vitro and in experimentally infected mice, resembling MHV (Arbour et al, 1999;Jacomy et al, 2006).…”
Section: Hcov-oc43mentioning
confidence: 95%
See 1 more Smart Citation
“…Unlike other alpha-and betacoronavirus species, BetaCoV1 and the related mouse hepatitis virus (MHV) and HCoV-HKU1 do not seem to have ancestral links to bats. Several recent descriptions of novel BetaCoV1 members or relatives in rodents suggest them as primordial hosts (Hu et al, 2017;Lau et al, 2015;Wang et al, 2015). HCoV-OC43 was found to have tropism for neural cells in vitro and in experimentally infected mice, resembling MHV (Arbour et al, 1999;Jacomy et al, 2006).…”
Section: Hcov-oc43mentioning
confidence: 95%
“…There are no conspecific virus sequences from any other animal species. However, as HCoV-HKU1 is a sister taxon to MHV and rat sialodacryoadenitis virus, and together with these stands in sister relationship to BetaCoV1 with its basal rodent-associated viruses, a primordial association with rodent hosts may be considered (Hu et al, 2017;Lau et al, 2015;Wang et al, 2015;Woo et al, 2005).…”
Section: Hcov-hku1mentioning
confidence: 99%
“…EF203064 to EF203067) are marked by "*". backbone replaced by a betaCoV S gene (Lau et al, 2007;Wang et al, 2015a). Furthermore, pairwise comparison of SeACoV genomic sequence with HKU2 indicated that the most dissimilar region was in the S gene, particularly, in the extreme NTD (aa 1-238).…”
Section: Complete Genomic Sequence Of the Emergent Seacov Revealed Itmentioning
confidence: 99%
“…However, analysis of the phylogenetic tree constructed based on the S genes (Fig. 4B) indicated that these six HKU2-related CoV strains along with a newly identified rat alphaCoV, LRNV (Wang et al, 2015a), formed a separate lineage clustered within the betaCoVs. The previous studies have suggested that HKU2 and the related LRNV probably resulted from an ancient recombination event with an alphaCoV genomic Fig.…”
Section: Complete Genomic Sequence Of the Emergent Seacov Revealed Itmentioning
confidence: 99%
“…Although bats, rodents, and birds act as the natural reservoir species for many coronaviruses (1)(2)(3), host range expansion into other species has been prevalent over the course of their evolutionary history. Known human coronaviruses likely originated as zoonotic pathogens that underwent host range expansion.…”
Section: Introductionmentioning
confidence: 99%